Teenage parents and their children—position paper of the European academy of paediatrics and the European confederation of primary care paediatricians - Fontoura-Matias, José; Chakhunashvili, Davit George; Copley, Sian; Dembiński, Łukasz; Drosdzol-Cop, Agnieszka; Hadjipanayis, Adamos; Reali, Laura; Mazur, Artur (Frontiers in Pediatrics, 2024)
Introduction Teenage parenthood presents multifaceted implications, affecting adolescent parents, their children, and extended families. Despite a decrease in teenage pregnancy rates across Europe, the phenomenon continues to present significant challenges, impacting not only the adolescent parents but also their offspring and extended families. Methods A comprehensive literature review was conducted. Key factors influencing teenage pregnancies, including socioeconomic background, family structure, and access to sex education and contraception, were examined. This review was supplemented by expert opinions from the European Academy of Paediatrics (EAP) and the European Confederation of Primary Care Paediatricians (ECPCP). Results The triad of mother, father, and child presents individual distinct healthcare needs and vulnerabilities, highlighting the importance of specialized support and healthcare. This paper explores the psychological, social, and educational repercussions of teenage parenthood on both parents and their children, including higher risks of postpartum depression, school dropout, and repeat pregnancies. Furthermore, it underscores the critical role that paediatricians and primary care providers play in supporting these young families. Discussion The position paper advocates for comprehensive care for adolescent parents and their children. It recommends preventive measures such as proper sex education and access to contraception to reduce unplanned teenage pregnancies. Additionally, it emphasizes the need for specialized healthcare and support for teenage parents to address their unique challenges and improve outcomes for both parents and their children.